Public Social Science at Work: Contesting Hostility Towards Nicaraguan Migrants in Costa Rica - Sandoval García, Carlos (2014)
Nicaraguan migration to Costa Rica is one of the most salient cases of South-South migration in Latin America. Despite Costa Rica’s self-representation as a peaceful and democratic society, Nicaraguan migrants in Costa Rica, the main foreign-born community in the country, are widely portrayed in derogatory terms, for example as violent and criminal and in general as “threatening Others” (Sandoval 2004). This chapter explores a set of examples of analyses of critical interventions – regarding immigration law, social imaginaries around which representations of Nicaraguans are framed, and participatory work carried out with impoverished communities – in order to reflect on the ways in which social sciences in Costa Rica attempt to intervene both in the everyday hostility of Costa Rican society and in the ways in which Nicaraguans contest that hostility. Responding to Michael Burawoy’s call for a “public sociology” (2005, 2007), the chapter reflects on how debates around public social sciences could enrich the political, institutional, and conceptual location of migration studies in Costa Rica.